Preterm birth and cardiometabolic risk factors in adolescence and early adulthood - Sipola-Leppänen, Marika (Oulun yliopisto, 2015)
About 11% of infants are born preterm (before 37 weeks of gestation) worldwide. Adults born preterm with very low birth weight show enhancement of cardiometabolic risk factors such as elevated blood pressure and impaired glucose regulation compared with their peers born at term. Not all the cardiometabolic risk factors related to preterm birth are known, or whether they apply to those born less preterm, although about 80% of premature infants are born late preterm. The association between preterm birth and cardiometabolic risk factors in adolescence and adulthood was investigated in three cohort studies: The Helsinki Study of Very Low Birth Weight Adults, the Northern Finland Birth Cohort 1986, and the ESTER study. Preterm birth over its whole range has a long-term impact on a child’s health in later life: adults born preterm with very low birth weight had lower resting energy expenditure, but higher resting energy expenditure per unit lean body mass than their peers born at term. Adolescent girls born before 34 weeks of gestation had higher blood pressure and boys have elevated levels of LDL cholesterol and apolipoprotein B. Adults born preterm were more likely to be obese and to have hypertension or metabolic syndrome than their peers born at term. In addition to conventional biomarkers of cardiometabolic disorders, they had alterations in other cardiometabolic biomarkers, such as uric acid and liver transaminases. Adolescents and adults born preterm are at greater risk of developing cardiometabolic disorders than their peers born at term. Most of the cardiometabolic risk factors related to preterm birth are modifiable. Favorable early life circumstances of premature infants, such as optimal nutrition and reduction of stress in neonatal intensive care units, might reduce the risk of later cardiometabolic disorders. In addition, children and adults born preterm might particularly benefit from primary prevention such as screening for additional risk factors and promotion of healthy lifestyles. Tiivistelmä Noin ...